PERBANDINGAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT DI BURSA EFEK INDONESIA 2014-2018 - Denia Septiana Wonggo; Hartaty Hadady; Rheza Pratama (Jurnal Manajemen Sinergi, 2021)
Objective: Comparison of Abnormal Stock Returns Before and After Stock Split on the Indonesia Stock Exchange. The sample in this study used a purposive method. Based on the sample selection in accordance with the specified criteria, the number of samples in this study were 40 companies or as many as 200 units of observation within a period of 5 years.Methodology: The analytical method used in this study is the Test Difference method.Finding: Hypothesis accepted at the 5% confidence level.Conclusion: The results showed that abnormal returns had a positive and significant effect before and after the stock split. Because an increase in abnormal stock returns before and after the stock split.